Healthcare-Associated Infections Controller: Concept Development - Karolayne Cabral Matias; Cyntia Leenara Bezerra da Silva; Hanna Priscilla da Silva Medeiros; Maria Isabel da Conceição Dias Fernandes; Dândara Nayara Azevêdo Dantas; Lays Pinheiro de Medeiros; Allyne Fortes Vitor (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To develop the concept of a Healthcare-Associated Infections Controller. Method: A qualitative methodological study, based on the Hybrid Model of Concept Development, conducted in three phases: Theoretical Phase (through a scoping review with a sample of 28 studies), Field Phase (online meeting with 30 professionals in the field), and Final Analytical Phase (data analysis and concept definition). Results: The antecedents, attributes, and consequences identified in the theoretical phase were similar to those described by the professionals. In the field phase, the majority of professionals defined “Infection Controller” as the most appropriate term for this professional. In the final analytical phase, the elements identified in the previous phases were similar; however, they had particularities. Final considerations: The concept of a Healthcare-Associated Infections Controller was developed, providing nurses with a better understanding of their role in care delivery and enhancing their awareness of their actions.